Physical, Physicochemical, Mechanical, and Sensory Properties of Bioplastics from Phosphate Acetylated Arenga Starches - Abdul Rahim; Safitri Dombus; Syahraeni Kadir; Muhardi Hasanuddin; Syamsuddin Laude; Jusman Aditya; Steivie Karouw (Polish Journal of Food and Nutrition Sciences)
Bioplastics are alternative to plastic packaging made from renewable natural materials. They have a great potential for wider application due to their environmental-friendliness and ease of degradation. This research, therefore, aimed to evaluate the physical, physicochemical, mechanical, and sensory characteristics of bioplastics made from native arenga starch (NAS) and phosphate acetylated arenga starch (PAAS). The PAAS was obtained by dual modification of NAS through acetylation using 5% acetic anhydride and crosslinking using a mixture of sodium trimetaphosphate (STMP) and sodium tripolyphosphate (STPP) at 99:1 ( w/w ). The concentrations of the mixture were varied at 2, 4, 6, 8, 10, and 12% ( w/w ) of the starch. The thickness, water holding capacity (WHC), oil holding capacity (OHC), water vapor transmission rate (WVTR), water content, biodegradation, Fourier transform infrared (FT-IR) spectroscopy, tensile strength, elongation at break, Young’s modulus, and sensory properties of the NAS and PAAS bioplastics were investigated. The results showed the thickness of the NAS and PAAS was generally uniform. The WHC of the NAS bioplastic was higher than that of PAAS. The OHC and WVTR of the PAAS bioplastics increased with the increment in the concentration of the STMP/STPP mixture. Furthermore, the water content of the PAAS bioplastics was lower than that of NAS, while the weight loss due to biodegradation of the NAS was higher compared to PAAS. The PAAS bioplastics were characterized by FTIR, which confirmed the acetylation and crosslinking between the arenga starch molecules. Generally, the elongation at break of the PAAS bioplastics was higher than that of the NAS bioplastic, color of the PAAS bioplastics was more transparent and texture of the PAAS bioplastics surface was smoother than of the NAS bioplastic.